Multiple Intimate Partner Violence Experiences: Knowledge, Access, Utilization and Barriers to Utilization of Resources by Women of the African Diaspora. - Sabri, Bushra; Huerta, Julia; Alexander, Kamila A; St Vil, Noelle M; Campbell, Jacquelyn C; Callwood, Gloria B (Journal of health care for the poor and underserved, 2015)
This study examined knowledge, access, utilization, and barriers to use of resources among Black women exposed to multiple types of intimate partner violence in Baltimore, Maryland and the U.S. Virgin Islands (USVI).